Estudio hidrológico para determinar el caudal de diseño de la presa del sistema de riego Cuñumbuza – Ledoy - Guerrero Ramírez, Walther Alonso (2010)
Water is the most abundant element on Earth, is the main constituent of all living things and is a major force It is-constantly <: ambiando .in -the superfide terr ~ stre. It is also a key element in the climate of our planet that favors human existence and have major influence on the progress of the civilization. Changes in the distribution, circulation or temperature $ waters on earth can have far-reaching effects; the glaciations, for example, were a manifestation of such effects. Human activities may cause some changes. The beings human plowing the soil, they irrigate crops, fertilize land, deforested forests, groundwater pumping, they build dams, shed waste into rivers and lakes, and do many other constructive things or destructive affecting circulation and water quality in the planet. Water, despite being one of the most important natural resources, is while the scarcest and variable in the territory of our country, especially on the coast and in fa s1erra, which are paradoxically regions settled predominantly human cultures and irrigated agriculture was developed. This scarcity and variability to our particular conditions must geographical, extremely diverse and rugged, and our Fluctuating weather conditions one of whose results are cycles periodic floods and droughts. Irrigation is a significant advance in the evolution of the As humanity on gender basis for the establishment of civilization. We can define irrigation water application as the man to cough Farmlands. It has technical characteristics, as there laws of water movement, the development of plants and other concurrent, man is capable of metering the quantities applied considering scientific principles. It also presents features art, especially in irrigation by gravity and at the time of application, as to the operational capacity of the irrigator. The water used for irrigation comes from natural sources. The sources It includes natural rainwater and surface runoff (lakes and rros). These resources should be used in a responsible manner and sustainable. The amount of water from rain depends on the weather conditions in the area. Surface water is a resource limited and normally requires the construction of reservoirs and prey for exploitation with a significant environmental impact. Efficiency in water use in irrigation is comprised of several components, considering the loss of this resource from its storage, driving up its application to the plots of irrigators. It is important to know how these components are defined, and how they can be improved to achieve optimization the use of this important and scarce resource in most agricultural areas. Hydrological changes in recent years have caused variations in the hydrological behavior of river basins, especially in Peru and the region of jungle. In this sense the irregularity in the availability of water of the major rivers, forces that have to execute works for use Water and it reaches to meet the requirements or demand throughout the year, even in times of low rainfall. For that planning, design, construction and implementation will be necessary appropriate infrastructure, the same as for dimensioning during the design phase needs to know the behavior of hydrological regime of the river, especially in regard to events external or avenues, hence the priority of determining the flow corresponding design, this being the case cunumbuza carriage in the San Martin region.